2022
DOI: 10.1002/hbm.26007
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation to modulate fMRI drug cue reactivity in methamphetamine users: A randomized clinical trial

Abstract: Transcranial direct current stimulation (tDCS) has been studied as a therapeutic option to alter maladaptive brain functions associated with chronic substance use.We present a randomized, triple-blind, sham-controlled, clinical trial to determine the neural substrates of tDCS effects on drug craving. Sixty participants with methamphetamine use disorder were assigned to two groups: active tDCS (5 x 7 cm 2 , 2 mA, 20 min, anode/cathode over the F4/Fp1) and sham stimulation. Neuroimaging data of a methamphetamine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 69 publications
0
17
0
1
Order By: Relevance
“…We included 110 studies, encompassing a total of 4820 participants . The majority of participants were male (2959 [61.4%] compared with 1861 females [38.6%]), and the mean (SD) age was 43 (8.8) years.…”
Section: Resultsmentioning
confidence: 99%
“…We included 110 studies, encompassing a total of 4820 participants . The majority of participants were male (2959 [61.4%] compared with 1861 females [38.6%]), and the mean (SD) age was 43 (8.8) years.…”
Section: Resultsmentioning
confidence: 99%
“…A pre-post tDCS-fMRI study on MUD participants showed a significant correlation between changes in brain functions in response to drug cues and the averaged EF strength solely in the frontopolar area, not other prefrontal regions (Esmaeilpour et al, 2019). A larger cohort of individuals with MUDs also showed similar results; a significant correlation was observed between the normal component of the EF and changes in functional activity in the frontopolar area during a standard drug cue reactivity task (Ekhtiari et al, 2022).…”
Section: Suds As a Sample Clinical Populationmentioning
confidence: 86%
“…However, similar to healthy participants, in both DLPFC montages, frontopolar received the highest EFs in the MUD group. This suggests the frontopolar area may play a role in tES over DLPFC for SUDs while much of the initial attention is focused on the DLPFC with more promising results with symmetric compared to asymmetric montages (Ekhtiari et al, 2022) Maybe the reason behind the significant rise in functional activity within VMPFC upon DLPFC stimulation is linked to the highest EF intensity in this particular brain area, which remains unexplored. Dose-response relationship analysis, which integrated head models with fMRI (refer to Supplementary materials section S7), found further support for the importance of EF strength in frontopolar area involvement in DLPFC stimulation for SUDs (Ekhtiari et al, 2022;Esmaeilpour et al, 2019).…”
Section: Suds As a Sample Clinical Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was conducted in accordance with the Declaration of Helsinki and all methods were carried out in accordance with relevant guidelines and regulations. More details on inclusion/exclusion criteria are in supplementary materials (Section S1) [42].…”
Section: Participantsmentioning
confidence: 99%